S36 Improving asthma care in the emergency department (ED): a 2-year prospective quality improvement (QI) project. (12th November 2019) - Long, G; Simpson, A; Stagg, K; Dutton, C; Jackson, H; Wood, G; Watson, L; Kane, B
Abstract : Introduction: The National Report of Asthma Deaths 2014 identified that of those who died, 21% had attended the ED at least once in the previous year. The Royal College of Emergency Medicine Asthma Audit (16/17) showed asthma care is falling well below national standards with 26% of patients having a peak expiratory flow (PEF) assessed. No national data exists to characterise high-risk patients seen, treated and discharged from ED. Objective: To characterise asthma patients treated and discharged from ED, and, through a prospective QI project, implement sequential interventions to increase the proportion of acute asthma patients who have a PEF within 30 minutes of arrival in ED to 80%. Methods: Over a 2-year period, we continuously collected data on demographics, pre- and post-treatment PEF, blood eosinophils and follow-up arrangements for consecutive adult patients presenting to Wythenshawe Hospital ED, coded with an asthma exacerbation. During this time, 7 QI Plan-Do-Study-Act (PDSA) cycles were carried out which focussed on staff engagement, education and use of the existing asthma pathway. Percentage of patients with PEF on arrival was plotted in a run chart. Results: 787 individual patients made 1038 visits to ED. ED staff treated and discharged 49.5% of patients. Of these, 12.9% were offered secondary care follow-up (compared with 58.7% of those admitted), 48.5% re-attended ED, 38.2% had blood eosinophils ≥300 cells/µL. The primary QI objective was achieved within 6 months (figure 1) through bespoke education delivered by the respiratory directorate, followed by weekly in-person reminders. However, this was not sustained due to factors such as winter pressures, staff turnover, introduction of a new electronic patient record and a move to a new ED building. Further PDSA cycles were implemented following recruitment of a central ED QI team, including introduction of a shortened asthma proforma and promotion of asthma care in daily staff huddles. Conclusion: Patients treated and discharged from ED had high levels of re-attendance, uncontrolled eosinophilia and were 4.5 times less likely to receive hospital follow-up than admitted patients. Sustained improvement in asthma assessment (such as PEF) was challenging and was supported by changes being driven by ED staff.